Online Education and Engineering Students' Perception of Pedagogical Quality, in Learning the Process Control Course with MATLAB - Omar Chamorro-Atalaya (Kassel University Press, 2021)
The objective of this article is describe the results obtained from the evaluation of perception in engineering students, regarding pedagogical quality, in the context of online education; during the learning process of the process control course with Matlab. When developing the research, it was determined with respect to the answers capacity factor, that the indicators that present a better perception are "When presenting an observation about the development of the subject, the teacher responds to it appropriately" and "When you have any question or concern, the teacher answers your query quickly”, which have a total agreement of 82.4%. Regarding the Empathy factor, the indicator that presents a better perception is “The time in which the subject is taught is convenient for all students”, which presents a total compliance of 72.7%. Regarding the indicators that show the quality of the pedagogical service in general, it was determined that 75.7% perceive that teachers are always willing to help them and 81.8% perceives that teachers understand the specific academic needs of their students.